TMF Attenuates Cognitive Impairment and Neuroinflammation by Inhibiting the MAPK/NF-κB Pathway in Alzheimer’s Disease: A Multi-Omics Analysis - Yonglin Liu; Xi Xu; Xiaoming Wu; Guodong Yang; Jiaxin Luo; Xinli Liang; Jie Chen; Yiguang Li (Marine Drugs)
The rising prevalence of Alzheimer’s disease (AD) underscores the urgent need for novel therapeutic agents derived from natural sources. Among flavonoids, 3′,4′,5,7-tetramethoxyflavone (TMF), a structural analog of luteolin, has gained attention for its favorable pharmacokinetics and potential neuroprotective properties. Despite the significant neuroprotective effects and favorable pharmacokinetics of TMF, its efficacy and mechanism of action in AD remain unclear. This study explored TMF’s pharmacological effects in AD models, highlighting its ability to improve memory and cognitive deficits in APP/PS1 mice. TMF reduced Aβ plaques, NFTs formation, and glial activation while suppressing neuroinflammation through the MAPK/NF-κB pathway. Further analysis in LPS-induced BV2 cells revealed TMF’s ability to reduce microglial activation. These findings highlight the anti-neuroinflammatory activity of TMF, suggesting its potential as a treatment for AD.